Transdermal administration of melatonin coupled to cryopass laser treatment as noninvasive therapy for prostate cancer. (1st January 2017) - Terraneo, Laura; Bianciardi, Paola; Virgili, Eleonora; Finati, Elena; Samaja, Michele; Paroni, Rita
Abstract: Melatonin, a pineal gland hormone, exerts oncostatic activity in several types of human cancer, including prostate, the most common neoplasia and the third most frequent cause of male cancer death in the developed world. The growth of androgen-sensitive LNCaP prostate cancer cells in mice is inhibited by 3 mg/kg/week melatonin (0.09 mg/mouse/week) delivered by i.p. injections, which is equivalent to a dose of 210 mg/week in humans. The aim of this study is to test an alternative noninvasive delivery route based on transdermal administration of melatonin onto the tumor area followed by cryopass-laser treatment. Two groups of immunodepressed mice were studied, one ( n = 10) subjected to 18 cryopass-laser therapy sessions and one ( n = 10) subjected to the same treatment without melatonin. These groups were compared with mice treated with i.p.-administered melatonin or vehicle with the same time schedule. We found that cryopass-laser treatment is as efficient as i.p. injections in reducing the growth of LNCaP tumor cells, affecting plasma melatonin and redox balance. Furthermore, both delivery routes share the same effects on the involved biochemical pathway driven by hypoxia-inducible factor 1α. However, cryopass-laser, as used in the present experimental setup, is less efficient than i.p delivery route in increasing the melatonin content and Nrf2 expression in the tumor mass. We conclude that cryopass-laser treatment may have impact for melatonin-based therapy of prostate cancer, by delivering drugs transdermally without causing pain and targeting directly on the site of interest, thereby potentially making long-term treatments more sustainable.